Breastfeeding Practices and Prevention of HIV Transmission from Mother to Child: Literature Study - Yersi Ahzani (MOLUCCAS HEALTH JOURNAL, 2022)
This study aims to describe the breastfeeding practices of mothers with HIV and prevention of HIV transmission from mother to child. The method used in this study is a literature study using the Online Science Direct Database, Clinical Key, Wiley, Scopus, Google Scholar, and ProQuest. The results showed that most mothers living with HIV have a desire to breastfeed. Several factors influence breastfeeding practices including the mother's level of knowledge, history of ante-natal care visits, income, perceptions of exclusive breastfeeding, and experience of experiencing problems during breastfeeding. Although HIV transmission from mother to child can occur, the rate of transmission can be reduced by routine and regular consumption of ARVs (Antiretrovirals) before or during pregnancy. Adequate educational services are needed by mothers to convince themselves to be able to practice breastfeeding safely.